Enhancing primary English writing with authentic learning in mobile cloud - Chin Da Bun Tiang; Mariam Mohamad; Mageswaran Sanmugam (Journal of Education and Learning (EduLearn), 2026)
This qualitative study examines the English writing experiences of 12 primary schoolchildren (PSC) from a vernacular school in Malaysia, employing Herrington and Kervin’s principles of authentic learning as its theoretical framework. Data were collected through in-depth one-on-one interviews, e-diaries, and unstructured non-participant observations, and analyzed using thematic analysis. The findings reveal that the participants effectively employed authentic learning strategies (AuLStra) in their writing activities, which included online reflective writing, collaborative online writing, and peer feedback. The use of AuLStra facilitated a collaborative environment where participants engaged in authentic writing tasks, benefiting from teacher scaffolding and peer assistance. Participants noted that reflecting on meaningful personal topics and engaging in creative writing through online collaboration significantly enhanced their writing fluency. The study highlights the impact of authentic learning practices on writing development and offers insights into the pedagogical and theoretical implications of integrating such strategies in primary education.